Dose Rationale for Amoxicillin in Neonatal Sepsis When Referral Is Not Possible - Salvatore D'Agate; Flora Tshinanu Musuamba; Oscar Della Pasqua (Frontiers Media S.A., 2020)
BackgroundDespite the widespread use of amoxicillin in young children, efforts to establish the feasibility of simplified dosing regimens in resource-limited settings have relied upon empirical evidence of efficacy. Given the antibacterial profile of beta-lactams, understanding of the determinants of pharmacokinetic variability may provide a more robust guidance for the selection of a suitable regimen. Here we propose a simplified dosing regimen based on pharmacokinetic-pharmacodynamic principles, taking into account the impact of growth, renal maturation and disease processes on the systemic exposure to amoxicillin.Materials and MethodsA meta-analytical modeling approach was applied to allow the adaptation of an existing pharmacokinetic model for amoxicillin in critically ill adults. Model parameterization was based on allometric concepts, including a maturation function. Clinical trial simulations were then performed to characterize exposure, as defined by secondary pharmacokinetic parameters (AUC, Cmax, Cmin) and T>MIC. The maximization of the T>MIC was used as criterion for the purpose of this analysis and results compared to current WHO guidelines.ResultsA two-compartment model with first order absorption and elimination was found to best describe the pharmacokinetics of amoxicillin in the target population. In addition to the changes in clearance and volume distribution associated with demographic covariates, our results show that sepsis alters drug distribution, leading to lower amoxicillin levels and longer half-life as compared to non-systemic disease conditions. In contrast to the current WHO guidelines, our analysis reveals that amoxicillin can be used as a fixed dose regimen including two weight bands: 125 mg b.i.d. for patients with body weight < 4.0 kg and 250 mg b.i.d. for patients with body weight ≥ 4.0 kg.ConclusionsIn addition to the effect of developmental growth and renal maturation, sepsis also alters drug disposition. The use of a model-based approach enabled the integration of these factors when defining the dose rationale for amoxicillin. A simplified weight-banded dosing regimen should be considered for neonates and young infants with sepsis when referral is not possible.